Effects of rhBMP-2 with various carriers on maxillofacial bone regeneration through computed tomography evaluation - Ja In Seo; Ji Hye Lim; Woo Min Jo; Jeong Keun Lee; Seung Il Song (SpringerOpen, 2023)
Abstract Background rhBMP-2 is regarded as the most potent osteoinductive growth factor, and it has been used in the oral cavity with different carriers. The purpose of this study is to evaluate the bone-regenerative effect of rhBMP-2 delivered with different carrier systems through three-dimensional cone beam computed tomography analysis. Method A total of 112 patients underwent oral surgery with rhBMP-2 application (Group 1, n = 53) or without rhBMP-2 application (Group 2, n = 59). Group 1 was divided into 3 groups according to carriers, rhBMP-2 with allograft (Group 1-1, n = 34), rhBMP-2 with xenograft (Group 1-2, n = 5), and rhBMP-2 with absorbable collagen sponge (Group 1-3, n = 14). Cone beam computed tomography scans were taken before surgery (T0) 6 months after surgery (T1). The volume of defects was measured through the three-dimensional image analysis tool. Results The average bone regeneration rate of Group 1 was significantly greater than that of Group 2. Within Group 1, the group that used allograft as a carrier (Group 1-1) showed significantly higher bone regeneration rates than the group that used absorbable collagen sponge as a carrier (Group 1-3). Conclusion The use of rhBMP-2 after oral surgery results in a superior bone regeneration rate compared to not using rhBMP-2, and its efficacy depends on the carriers it is used with. Allograft affects bone regeneration more than absorbable collagen sponge when it is carried with rhBMP-2. Therefore, the appropriate use of rhBMP-2 with suitable bone grafting materials is useful for promoting postoperative bone regeneration in oral surgery.